Clinical significance of periventricular leukomalacia in the formation cerebral palsy - O. K. Kirilochev; Z. G. Tarasova; A. S. Eiberman; L. G. Bochkova (Лечащий Врач, 2023)
Background. Cerebral palsy is one of the main causes of childhood disability. In this case, the main form of brain damage is periventricular leukomalacia, the preferred diagnostic method for which is ultrasound.   Objective. Objective of the study: to study the features of the course, the nature of structural changes and the clinical significance of periventricular leukomalacia in the formation of cerebral palsy. The study design wasa prospective, observational, single-center study.   All patients were initially in the intensive care unit due to the presence of multiple organ failure. Inclusion criteria: newborns with perinatal lesions of the central nervous system in combination with structural changes in the brain according to ultrasound. Exclusion criteria: newborns with perinatal lesions of the central nervous system with no structural changes in the brain according to ultrasound. Clinical observation of patients began in the neonatal period. Subsequently, dynamic observation was carried out with an assessment of the state of the nervous system up to 4 years. For an objective assessment of the psychomotor development of children in the first year of life, the method of quantitative assessment of the child's age development according to the L. T. Zhurba and E. A. Mastyukova.   Results. 115 patients were under observation (full-term – 31, premature – 84). Forming and formed cerebral palsy was diagnosed in 20 patients. The leading nosological form of damage to the central nervous system in the neonatal period in patients was cerebral ischemia (95 %). In 80 % of patients, structural changes in the brain, according to ultrasound, were in the form of periventricular leukomalacia. Both non-cystic forms (10 patients) and cystic forms (6) were identified. The level of psychomotor development according to L. T. Zhurba and E. A. Mastyukova at the age of 3 months was 6.8 ± 0.65 points; at 6 months – 8.9 ± 0.77 points; at 1 year – 12.2 ± 0.78, which indicated a total gross delay in psychomotor development in the first year of life. In patients with cerebral palsy at the age of 1-year, atrophic dropsy of the brain was recorded with the presence of a pathognomonic sign – expansion of the third ventricle in proportion to the lateral ventricles of the brain, which is associated with a deficiency of oligodendroglia and myelin in periventricular leukomalacia. In 16 surviving children, the following organic lesions of the central nervous system were formed: cerebral palsy, severe double hemiplegia, symptomatic epilepsy (5 children; 31.3 %); cerebral palsy, severe double hemiplegia (5 children; 31.3 %); cerebral palsy, spastic diplegia (6 children; 37.4 %).